Coated modified sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
By using Na2V3O7 coating on the positive electrode material of sodium ion battery, the problems of phase change and vacancy ordering at high voltage are solved, and the capacity retention rate and electrochemistry of the battery are improved Performance, achieving improvements in structural stability and charge transfer efficiency.
Patent Information
- Application Number
- CN202411474479.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-20
AI Technical Summary
The positive electrode material of sodium ion battery is prone to phase change and Na+ vacancy ordering at high voltage, resulting in capacity attenuation, and the electrolyte oxidation under high voltage conditions, destroying the positive electrode structure and reducing electrochemical performance.
The sodium transition metal oxide of O3 phase was modified by Na2V3O7 coating layer. The sodium and vanadium sources were dispersed in a non-aqueous solvent in a protective atmosphere and stirred with the sodium transition metal oxide of O3 phase, and then sintered to form a coating. Modify the positive electrode material of sodium ion battery to improve the structural stability and charge transfer efficiency of the material.
It effectively improves the discharge capacity and capacity retention rate of the first circle of the battery, improves the circulation performance and structural stability of the positive electrode material, enhances the electrochemical performance, and simplifies the preparation process.
Smart Images

Figure CN119170780A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials for sodium ion batteries, and in particular relates to the modification of positive electrode materials. Background Art
[0002] Since the standard electrode potential of sodium (-2.71 V) is greater than that of lithium (-3.04 V), sodium-ion batteries are more stable during the cycle and safer in application. Therefore, sodium-ion batteries, which have the advantages of low cost, environmental friendliness, high energy density and high safety, are favored by researchers.
[0003] However, the cathode materials of sodium ion batteries are prone to phase transition and Na + Vacancy ordering is the main reason for capacity decay. Phase transition changes the material structure, hindering the Na + Diffusion. In addition, high pressure conditions will accelerate the oxidation of the electrolyte, destroy the structure of the positive electrode, and lead to the attenuation of electrochemical performance. To solve the above problems, electrochemically active or inactive coating materials are usually used to coat the surface of the positive electrode material to reduce harmful side reactions by inhibiting direct contact between the positive electrode and the electrolyte. Summary of the invention
[0004] In response to the above technical problems, the present application provides a coated modified sodium ion battery positive electrode material and a preparation method thereof, and a secondary battery.
[0005] To achieve the above objectives, this application proposes the following technical solutions: In a first aspect, a coated modified sodium ion battery positive electrode material is provided, comprising an O3 phase sodium transition metal oxide matrix and a coating layer located on at least a portion of the surface of the O3 phase sodium transition metal oxide matrix, wherein the coating layer is Na2V3O7.
[0006] Preferably, the chemical formula of the O3 phase sodium transition metal oxide is NaNi x Fe y Mn 1-x-y O2, where 0.2≤x≤0.5, 0.1≤y≤0.4.
[0007] Preferably, the mass ratio of the coating layer to the O3 phase sodium transition metal oxide is 0.5~2%:1.
[0008] In a second aspect, a method for preparing a coated modified sodium ion battery positive electrode material is provided, comprising: A sodium source and a vanadium source are dispersed in a non-aqueous solvent under a protective atmosphere, and then an O3 phase sodium transition metal oxide is added, stirred evenly, and then the non-aqueous solvent is evaporated with stirring to obtain a solid, and the solid is dried to obtain a mixture; the mixture is sintered under an inert atmosphere to obtain a Na2V3O7 coated modified sodium ion battery positive electrode material.
[0009] Preferably, the sintering temperature is 600-900° C.; the sintering time is 20-24 hours; and the sintering is performed in a tubular furnace filled with argon gas.
[0010] Preferably, the molar ratio of sodium in the sodium source to vanadium in the vanadium source is 2-2.2:3.
[0011] Preferably, the sodium source is one or more of sodium acetate, sodium carbonate, sodium oxalate, sodium bicarbonate, sodium nitrate, etc.; the vanadium source is one or both of vanadium trioxide and vanadium dioxide.
[0012] Preferably, the non-aqueous solvent is anhydrous ethanol.
[0013] Preferably, the protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
[0014] In a third aspect, a sodium ion battery is provided, comprising the aforementioned coated modified sodium ion battery positive electrode material or the coated modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0015] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects: The use of Na2V3O7 to coat modified O3 phase sodium transition metal oxide can effectively improve the first cycle discharge capacity and capacity retention rate of the battery.
[0016] By in-situ coating Na2V3O7 on the surface of O3 phase sodium transition metal oxide, it is beneficial to further improve the structural stability of the coated modified O3 phase sodium transition metal oxide and improve the performance of the modified positive electrode material. In addition, the coating method is simple, effective and easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 This is the XRD pattern of the coated modified positive electrode material obtained in Example 1.
[0019] Figure 2 This is the SEM image of the coated modified positive electrode material obtained in Example 1.
[0020] Figure 3 is the XRD pattern of the coating layer.
[0021] Figure 4 The positive electrode material prepared in Examples 1 to 4, Na2V3O7 material, NaNi 0.3 Fe 0.3 Mn 0.4 O2 materials and NaNi 0.5 Fe 0.2 Mn 0.3 Cycling curves of batteries assembled with O2 materials. DETAILED DESCRIPTION
[0022] The present invention provides a coated modified sodium ion battery positive electrode material, comprising an O3 phase sodium transition metal oxide matrix and a coating layer located on at least a portion of the surface of the O3 phase sodium transition metal oxide matrix, wherein the coating layer is Na2V3O7.
[0023] The present application uses Na2V3O7 to coat and modify the O3 phase sodium transition metal oxide, which can enhance the charge transfer and sodium ion transmission between the O3 phase sodium transition metal oxide and the electrolyte, reduce the interface impedance, and maintain good structural stability during repeated charge and discharge, thereby improving the cycle performance of the O3 phase sodium transition metal oxide. In addition, the +4 valence V in Na2V3O7 can undergo redox reactions during the battery charge and discharge process, thereby enhancing the working voltage and theoretical capacity of the O3 phase sodium transition metal oxide.
[0024] In some embodiments, the chemical formula of the O3 phase sodium transition metal oxide is NaNi x Fe y Mn 1-x-y O2, where 0.2≤x≤0.5, 0.1≤y≤0.4.
[0025] In some preferred embodiments, the mass ratio of the coating layer to the O3 phase sodium transition metal oxide is 0.5-2%:1. If the coating amount is too low, the modification effect is not obvious. If the coating amount is too large, volume expansion and contraction are likely to occur, resulting in stress concentration, which will deteriorate the structural stability of the positive electrode material. The applicant has studied that when the mass ratio of the coating layer to the O3 phase sodium transition metal oxide is 0.5-2%:1, the effect of improving the structural stability and electrical properties of the positive electrode material is the best.
[0026] The present invention provides a method for preparing a coated modified sodium ion battery positive electrode material, comprising: A sodium source and a vanadium source are dispersed in a non-aqueous solvent under a protective atmosphere, and then an O3 phase sodium transition metal oxide is added, stirred evenly, and then the non-aqueous solvent is evaporated with stirring to obtain a solid, and the solid is dried to obtain a mixture; the mixture is sintered under an inert atmosphere to obtain a Na2V3O7 coated modified sodium ion battery positive electrode material.
[0027] In some preferred embodiments, the sintering temperature is 600-900°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc.; the sintering time is 20-24h; and the sintering is carried out in a tubular furnace with argon. The applicant has found through research that when the sintering temperature is too low, it is difficult to obtain the Na2V3O7 coating layer, and when the sintering temperature is too high, it is easy to cause the specific capacity and cycle performance of the modified positive electrode material to decrease. The applicant has studied and found that when the sintering temperature is 600-900°C, and more preferably 600-750°C, the structural stability and electrical performance of the positive electrode material are best improved.
[0028] In some preferred embodiments, the molar ratio of sodium in the sodium source to vanadium in the vanadium source is 2-2.2:3.
[0029] In some embodiments, the sodium source is one or more of sodium acetate, sodium carbonate, sodium oxalate, sodium bicarbonate, sodium nitrate, and the like.
[0030] In some embodiments, the vanadium source is one or more of vanadium trioxide and vanadium dioxide.
[0031] In some preferred embodiments, the non-aqueous solvent is anhydrous ethanol, which is stable, cheap and easily available. The non-aqueous solvent can be used in a conventional amount, as long as it can be evenly dispersed so that the coating is relatively uniform. Usually, the mass ratio of the solid material to the solvent is about 1:20 to 50 during the experiment.
[0032] In some embodiments, the chemical formula of the O3 phase sodium transition metal oxide is NaNi x Fe y Mn 1-x-y O2, where 0.2≤x≤0.5, 0.1≤y≤0.4.
[0033] The stirring and evaporating temperature can be a conventional temperature in the art, as long as the evaporation temperature is higher than the boiling point of the non-aqueous solvent, which can be 80-120°C.
[0034] In order to improve the stability of the positive electrode material, the drying is preferably vacuum drying; and the drying temperature is 60-80°C.
[0035] The protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere, such as argon, helium, etc.
[0036] In some preferred embodiments, the Na2V3O7 is 0.5-2% of the mass of the O3 phase sodium transition metal oxide, for example, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc.
[0037] The present invention provides a sodium ion battery, comprising the aforementioned coated modified sodium ion battery positive electrode material or the coated modified sodium ion battery positive electrode material prepared by the aforementioned preparation method.
[0038] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.
[0039] Example 1 Step 1: In a glove box filled with argon, sodium carbonate and vanadium trioxide are uniformly dispersed in 120 ml of anhydrous ethanol at a molar ratio of 2:3; Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 0.5% (i.e. the design target coating material is 0.5% of the core material mass) 0.3 Fe 0.3 Mn 0.4 O2 was dispersed in the solution of step 1, stirred for 1 h, transferred to an oil bath and evaporated at 80 °C, then taken out and dried in a vacuum drying oven at 60 °C overnight; Step 3: Heat the product of step 2 in an argon tube furnace at 600°C for 20 hours to obtain a positive electrode material coated with Na2V3O7. The XRD pattern of the obtained coated modified positive electrode material is as follows: Figure 1 As shown in the figure, it can be seen that the product is a pure O3 phase with no obvious impurity peaks. The SEM image of the obtained coated modified positive electrode material is shown in Figure 2 As shown, from Figure 2 It can be seen that the material is a flake-shaped single crystal with a tubular coating on the surface.
[0040] The composition and structure of the coating layer are known, and the coating layer is prepared by the following method: Step 1: In a glove box filled with argon, evenly disperse sodium carbonate and vanadium trioxide in 120 ml of anhydrous ethanol at a molar ratio of 2:3; transfer to an oil bath pot and evaporate to dryness at 80°C, then take out and dry in a vacuum drying oven at 60°C overnight; Step 2: Heat the product of step 1 in an argon tube furnace at 600°C for 20 hours to obtain a coating material. The XRD pattern of the coating layer is as follows: Figure 3 As shown, from Figure 3It can be seen that the coating layer conforms to the characteristic peaks of Na2V3O7 and has no obvious impurity phase, indicating that the coating layer is Na2V3O7.
[0041] Example 2 Step 1: In a glove box filled with argon, sodium oxalate and vanadium trioxide are uniformly dispersed in 200 ml of anhydrous ethanol at a molar ratio of 2:3; Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 1.2% 0.3 Fe 0.3 Mn 0.4 O2 was dispersed in the solution of step 1, stirred for 2 h, transferred to an oil bath and evaporated to dryness at 120 °C, and then taken out and dried in a vacuum drying oven at 80 °C overnight; Step 3: Heat the product of step 2 in an argon tube furnace at 700°C for 24 hours to obtain a positive electrode material coated with Na2V3O7.
[0042] Example 3 Step 1: In a glove box filled with argon, sodium carbonate and vanadium trioxide are uniformly dispersed in 180 ml of anhydrous ethanol at a molar ratio of 2:3; Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 0.5% 0.5 Fe 0.2 Mn 0.3 O2 was dispersed in the solution of step 1, stirred for 2 h, transferred to an oil bath and evaporated to dryness at 100 °C, and then taken out and dried in a vacuum drying oven at 70 °C overnight; Step 3: Heat the product of step 2 in an argon tube furnace at 900°C for 24 hours to obtain a positive electrode material coated with Na2V3O7.
[0043] Example 4 Step 1: In a glove box filled with argon, sodium carbonate and vanadium trioxide are uniformly dispersed in 120 ml of anhydrous ethanol at a molar ratio of 2:3; Step 2: Weigh the O3 phase core material NaNi according to the coating ratio of 2% 0.3 Fe 0.3 Mn 0.4 O2 was dispersed in the solution of step 1, stirred for 1 h, transferred to an oil bath and evaporated at 80 °C, then taken out and dried in a vacuum drying oven at 60 °C overnight; Step 3: Heat the product of step 2 in an argon tube furnace at 800°C for 20 hours to obtain a positive electrode material coated with Na2V3O7.
[0044] Comparative Example 1 Step 1: In a glove box filled with argon, sodium carbonate and vanadium trioxide are uniformly dispersed in 120 ml of anhydrous ethanol at a molar ratio of 2:3; Step 2: Heat the product of step 1 in an argon tube furnace at 600°C for 20 hours to obtain Na2V3O7 material.
[0045] Preparation of the battery: The positive electrode materials prepared in each example, the Na2V3O7 material prepared in Comparative Example 1, and the NaNi 0.3 Fe 0.3 Mn 0.4 O2 materials, NaNi 0.5 Fe 0.2 Mn 0.3 The O2 material was mixed with the conductive agent Super P and the binder PVDF in a ratio of 8:1:1 and then coated on the surface of the aluminum foil. After the surface slurry dried, it was placed in a vacuum oven at 80°C for drying; then the button battery was assembled in a glove box with an Ar atmosphere. The negative electrode of the button battery was Na foil, and the diaphragm was Whatman GF / D glass fiber. The electrolyte used was a 1 M NaClO4 solution of 5% fluoroethylene carbonate (FEC) + 95% propylene carbonate (PC). The charge and discharge test was carried out on the Blue Electric test system, with a test voltage range of 2~4V, a current density of 1C, and 50 cycles.
[0046] The positive electrode materials prepared in Examples 1 to 4, the Na2V3O7 materials prepared in Comparative Example 1, and the two core materials NaNi 0.3 Fe 0.3 Mn 0.4 O2 materials and NaNi 0.5 Fe 0.2 Mn 0.3 The cycle curve of the battery assembled with O2 materials is as follows Figure 4 As shown, from Figure 4 It can be seen that the discharge capacity of the battery assembled with Na2V3O7 material is 86mAh / g, and the capacity retention rate after 50 cycles is 95.23%, which has good stability but low capacity. Figure 4 It can also be seen that after the positive electrode materials prepared in Examples 1 to 4 and the two core materials are assembled into batteries, the first cycle discharge capacities are 125.1 mAh / g, 123.9 mAh / g, 129.9 mAh / g, and 126.6 mAh / g, respectively, and the capacity retention rates after 50 cycles are 92.32%, 88.94%, 88.76%, and 85.62%, respectively. 0.3 Fe 0.3 Mn 0.4 O2 and NaNi 0.5 Fe 0.2 Mn 0.3The discharge capacity of the battery assembled with O2 is 122.8mAh / g and 126.5mAh / g respectively, and the capacity retention rate after 50 cycles is 71.73% and 75.26% respectively. It can be seen that the battery assembled with the coated modified positive electrode material prepared in each embodiment has a better first-cycle discharge capacity and capacity retention rate than the battery assembled with the unmodified positive electrode material. After analysis, this may be because the coating and modification of the O3 phase sodium transition metal oxide with Na2V3O7 can enhance the charge transfer and sodium ion transmission between the O3 phase sodium transition metal oxide and the electrolyte, reduce the interface impedance, and maintain structural stability during repeated charge and discharge, thereby improving the cycle performance of the O3 phase sodium transition metal oxide; and the +4 valence V in Na2V3O7 can undergo redox reaction during the battery charge and discharge process, thereby enhancing the working voltage and theoretical capacity of the O3 phase sodium transition metal oxide.
[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coated modified sodium ion battery positive electrode material, characterized in that: It comprises an O3 phase sodium transition metal oxide matrix and a coating layer located on at least a portion of the surface of the O3 phase sodium transition metal oxide matrix, wherein the coating layer is Na2V3O7.
2. The coated modified sodium ion battery positive electrode material according to claim 1, characterized in that: The chemical formula of the O3 phase sodium transition metal oxide is NaNi x Fe y Mn 1-x-y O2, where 0.2≤x≤0.5, 0.1≤y≤0.4; The mass ratio of the coating layer to the O3 phase sodium transition metal oxide is 0.5-2%:
1.
3. The method for preparing the coated modified sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: include: A sodium source and a vanadium source are dispersed in a non-aqueous solvent under a protective atmosphere, and then an O3 phase sodium transition metal oxide is added, and after stirring evenly, the non-aqueous solvent is evaporated with stirring to obtain a solid, and the solid is dried to obtain a mixture; the mixture is sintered under an inert atmosphere to obtain a Na2V3O7 coated modified sodium ion battery positive electrode material.
4. The method for preparing the coated modified sodium ion battery positive electrode material according to claim 3, characterized in that: The sintering temperature is 600-900° C.; the sintering time is 20-24 hours; and the sintering is carried out in a tubular furnace with argon gas.
5. The method for preparing the coated modified sodium ion battery positive electrode material according to claim 3, characterized in that: The molar ratio of sodium in the sodium source to vanadium in the vanadium source is 2-2.2:
3.
6. The method for preparing the coated modified sodium ion battery positive electrode material according to claim 3, characterized in that: The sodium source is one or more of sodium acetate, sodium carbonate, sodium oxalate, sodium bicarbonate, and sodium nitrate; The vanadium source is one or both of vanadium trioxide and vanadium dioxide.
7. The method for preparing the coated modified sodium ion battery positive electrode material according to claim 3, characterized in that: The non-aqueous solvent is anhydrous ethanol; The protective atmosphere is a nitrogen atmosphere or an inert gas atmosphere.
8. A sodium ion battery, characterized in that It includes the coated modified sodium ion battery positive electrode material as described in claim 1 or 2, or the coated modified sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 3 to 7.
